Purchasing practices of selected resorts in Tanza, Cavite: a qualitative study. - Vallega, Ailene B.; Limbaga, Clifford P. (Parañaque City; Olivarez College, 2006)
Statement of the problem The study tried to compare the purchasing procedure in linen in Tanza, Cavite. Specifically, it tried to answer the following question: 1. Who were responsible in purchasing linen? 1.1 Marketer 1.2 Marketing Department 1.3 Marketer 1.4 Marketing Department 1.5 Purchasing Department 2. What was method used in purchasing linen? 2.1 Indirect Buying 2.2 Seal Bidding 2.3 Canvassing 2.4 Canvassing 2.5 Canvassing 3. What was the standard requirement followed in purchasing linen? 4. How many times they purchase linen? 5. What was the procedure followed in purchasing? 6. What was the time allotted in purchasing linen? Research Method The qualitative method was use in this study specifically, it was used in the survey and documentary analysis to come up with an objective quality purchasing of linen in tanza, cavite. Subject of the study The study involves 5 resorts located in tanza, cavite. Which were categories moderately performing and low performing resorts. Research Instruments The sole instruments used in this study to gather information from the respondent was a questionnaire. The formulation of the questionnaire was a results of intensive reading of conceptual and research literature and other similar materials that contributed to the idea indicated in the questionnaire.
Undergraduate Thesis